The Hidden Face of Wine Polyphenol Polymerization Highlighted by High‐Resolution Mass Spectrometry. Issue 3 (15th May 2017) - Vallverdú‐Queralt, Anna; Meudec, Emmanuelle; Eder, Matthias; Lamuela‐Raventos, Rosa M.; Sommerer, Nicolas; Cheynier, Véronique
Abstract: Polyphenols, including tannins and red anthocyanin pigments, are responsible for the color, taste, and beneficial health properties of plant‐derived foods and beverages, especially in red wines. Known compounds represent only the emerged part of the "wine polyphenol iceberg". It is believed that the immersed part results from complex cascades of reactions involving grape polyphenols and yeast metabolites. We used a non‐targeted strategy based on high‐resolution mass spectrometry and Kendrick mass defect plots to explore this hypothesis. Reactions of acetaldehyde, epicatechin, and malvidin‐3‐ O ‐glucoside, representing yeast metabolites, tannins, and anthocyanins, respectively, were selected for a proof‐of‐concept experiment. A series of compounds including expected and so‐far‐unknown structures were detected. Random polymerization involving both the original substrates and intermediate products resulting from cascade reactions was demonstrated. Abstract : Two plus one makes an infinity : Non‐targeted strategies based on high‐resolution mass spectrometry and Kendrick mass defect plots demonstrate that random cascade reactions in a simple wine‐like model system consisting of anthocyanins, epicatechin, and acetaldehyde generate high complexity. Wine composition likely results from similar step growth condensation and polymerization reactions involving additional building blocks and reactions